Porcine sapoviruses: Pathogenesis, epidemiology, genetic diversity, and diagnosis - Nagai, Makoto (Virus Res, 2020)
The first porcine Sapovirus (SaV) Cowden strain was discovered in 1980. To date, eight genogroups (GIII, V-IX) and three genogroups (GIII, GV, and GVI) of porcine SaVs have been detected from domestic pigs worldwide and wild boars in Japan, respectively based on the capsid sequences. Although GIII Cowden strain replicated in the villous epithelial cells and caused intestinal lesions in the proximal small intestines (mainly in duodenal and less in jejunum), leading to mild to severe diarrhea, in the orally inoculated neonatal gnotobiotic pigs, the significance of porcine SaVs in different ages of pigs with diarrhea in the field is still undetermined. This is due to two reasons: 1) similar prevalence of porcine SaVs was detected in diarrheic and non-diarrheic pigs; and 2) co-infection of porcine SaVs with other enteric pathogens is common in pigs. Diagnosis of porcine SaV infection is mainly based on the detection of viral nucleic acids using reverse transcription (RT)-PCR and sequencing. Much is unknown about these genetically diverse viruses to understand their role in pig health and to evaluate whether vaccines are needed to prevent SaV infection.